Machine translation for financial news. (4th August 2014) - Wan, Y.S.; Tan, C.L.; Teht, H.H.; Pang, B.T.
This paper proposes a machine translation method which involves interleaving analysis, transfer and synthesis in incremental stages. The general approach is to translate as much as possible whenever the necessary information is available, while extra work is done only when more information must be obtained for the translation to proceed. Based on this method, a prototype for English–Chinese financial news translation has been implemented. It is intended to be a computer–aided system which produces output that requires human touch–ups.